2019
DOI: 10.1039/c9mt00248k
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer activities of metal-based complexes by regulating the VEGF/VEGFR2 signaling pathway and apoptosis-related factors Bcl-2, Bax, and caspase-9 to inhibit angiogenesis and induce apoptosis

Abstract: Copper-based complexes exhibited multiple anti-cancer functions by regulating the expressions of Bcl-2, Bax, and caspase-9 and activating the VEGF/VEGFR2 signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Copper is indispensable in the angiogenesis process, the administration of copper sequestering agents as an antitumor approach is under evaluation [5][6][7]. During the angiogenesis process, copper translocates from intracellular to extracellular space [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copper is indispensable in the angiogenesis process, the administration of copper sequestering agents as an antitumor approach is under evaluation [5][6][7]. During the angiogenesis process, copper translocates from intracellular to extracellular space [55].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study regarding the evaluation of novel copper-based complexes was conducted. It showed remarkable activities, both in vitro and in vivo, as a potential anti-cancer and anti-angiogenesis copper-containing drug [7].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that low VEGF levels downregulated the antiapoptotic factor B‐cell lymphoma‐2 (Bcl‐2), 21 but upregulated the pro‐apoptotic factor BCL2‐associated X (Bax) 22 . The expression levels of apoptosis‐related proteins (caspase‐3, caspase‐8, caspase‐9, Bax, Bcl‐2 and VEGF) were detected via immunofluorescence analysis to investigate the antitumour mechanism of SNP.…”
Section: Resultsmentioning
confidence: 99%
“…Caspase9 can be activated in the mitochondrial apoptotic pathway and becomes its active form cleaved-caspase9, which plays an important role in the execution of apoptosis. 34 Studies have shown that PUFA promotes the apoptosis of colorectal cancer cells by inhibiting the expression of Bcl-2 and promoting the activation of caspase9. 35 In this study, we found that Omega-3PUFA inhibits the expression of Bcl-2 in colorectal cancer in vitro and in vivo, and promotes cleaved-caspase9 expression.…”
Section: Discussionmentioning
confidence: 99%